BAKTERI ENDOFIT KULIT BATANG TERAP (ARTOCARPUS ELASTICUS) DAN AKTIFITASNYA SEBAGAI ANTIBAKTERI - Guplin -; Dwi Soelistya Dyah Jekti; Lalu Zulkifli (Jurnal Penelitian Pendidikan IPA, 2017)
This study aims to identify the types of endophytic bacteria on the bark of terap (Artocarpus elasticus) capable of inhibiting the growth of clinical isolate bacteria of Staphylococcus aureus, Escherichia coli, Salmonella typhi, and Pseudomonas aeruginosa. Stages of this study were (1) isolating the endophytic bacteria from the bark of terap plants (2) antibacterial test (inhibition test) against clinical isolate bacteria, (3) biochemical test upon endophytic isolate bacteria showing strong  inhibition effect, (4) moleculer identifcation upon endophytic bacteria isolate showing strong  inhibition effect. From this study, it was obtained 34 barks of terap isolates, and 12 isolates have inhibitory effect on S. aureus. Based on 16S rRNA   molecular identification, the isolate of endophytic bacteria of the barks were identified as Bacillus cereus, Bacillus subtilis and Bacillus amyloliquefaciens. Those  endophytic bacteria of Terap plants  are potentially  to be  developed as a the producer of antibacterial compounds.Keywords: Terap bark, Endophytic bacteria, Identification, Antibacteria